Rancang Bangun Sistem Injeksi Sepeda Motor 4 Langkah - Wahyu Danang Veby Yansyah; Wawan Purwanto; Hasan Maksum; Ahmad Arif; Irma Wirantina Kustanrika; Syalsa Billa Ahmad (Universitas Negeri Padang, 2024)
This study discusses the design of a four stroke motorcycle injection system with the aim of reducing harmful substances in exhaust emissions by changing the conventional system to an EFI system and to determine the torque and power and fuel consumption produced. This research method uses the experimental method. The results of this study are the power produced in the designed EFI system decreased by 4.33% with a difference of 0.23 kW, torque decreased by 6.95% with a difference of 0.57 kW, and the content of HC exhaust emissions decreased by 394.58% with a difference of 365.66 ppm, CO content decreased by 39.13%, with a difference of 0.63%, the content of CO2 in exhaust emissions on a four stroke motorcycle that was converted to an EFI system increased by 68.99% with a difference of 2.67%, and fuel consumption was getting smaller so that it increased by 31.85% with a difference of 21.98 Km/ L. Penelitian ini membahas tentang rancang bangun sistem injeksi sepeda motor 4 langkah dengan tujuan mengurangi zat berbahaya dalam emisi gas buang dengan mengubah sistem konvensional menjadi sistem EFI dan untuk menentukan torsi, daya, dan konsumsi bahan bakar yang dihasilkan. Metode penelitian ini menggunakan metode eksperimental. Hasil penelitian ini menunjukkan bahwa daya yang dihasilkan dalam sistem EFI yang dirancang menurun sebesar 4,33% dengan selisih 0,23 kW, torsi menurun sebesar 6,95% dengan selisih 0,57 Nm, dan kandungan emisi HC menurun sebesar 394,58% dengan selisih 365,66 ppm, kandungan CO menurun sebesar 39,13% dengan selisih 0,63%, kandungan CO2 dalam emisi gas buang pada sepeda motor 4 langkah yang dikonversi menjadi sistem EFI meningkat sebesar 68,99% dengan selisih 2,67%, dan konsumsi bahan bakar menjadi lebih kecil sehingga meningkat sebesar 31,85% dengan selisih 21,98 km/L.